Development of an Analytical Method for Kasugamycin Residue in Herbal Medicine, Achyranthes japonica Nakai - Jeong Yoon Choi; Hun Ju Ham; Min-woo Kim; Abd Elaziz Sulieman Ahmed Ishag; Jang-Hyun Hur (Indonesian Journal of Chemistry, 2022)
This study developed a suitable analytical method for kasugamycin residues in Achyranthes japonica using LC/MS/MS equipped with an amide column for polar substances. Extraction and cleanup processes were done at pH 4.5–5. Purification efficiency was assessed and confirmed step by step by selecting silica, hydrophilic-lipophilic balance (HLB), strong cation exchange (SCX), and double (HLB and SCX) cleanup SPE cartridges. The results indicated that silica SPE cartridge exhibited overloading tendency, while HLB SPE cartridge had low cleaning efficiency. Among SPE cartridges used, double cleanup and SCX were found sufficient with respective matrix effects of –15% and +14%, respectively. The LOD and LOQ were 0.008 ng and 0.04 mg/kg, respectively. The correlation coefficient (R2) was higher than 0.99, recovery rate ranges were 86.3–97.2%, and the RSD was below 8.8%. All methods are consistent with the Codex guidelines criteria. This study developed an appropriate LC/MS/MS analytical method for kasugamycin residue analysis in A. japonica with optimized, efficient extraction and purification conditions using a single SCX SPE cartridge, which is simple and time-efficient. In addition, the HLB and SCX SPE cartridges of the double cleanup methods were identified as primary methods that can be applied for the cleanup of other medicinal herbs.